Reviews/Interviews - Sumera, Adam; Pietrzak, Wit; Kocot, Monika; Faqir, Fadia; Assif, Maria; Ravvin, Norman; Majer, Krzysztof (Text Matters: A Journal of Literature, Theory and Culture, 2012)
Adam Sumera: Capital Ellowen Deeowen: A Review of The Making of London: London in Contemporary Literature by Sebastian Groes (Houndsmills: Palgrave-Macmillan, 2011) Wit Pietrzak: Deconstruction and Liberation: A Review of Simon Glendinning’s Derrida (New York: Oxford UP, 2011) Monika Kocot: Authenticity, Transdifference, Survivance: Native American Identity (Un)Masked: A Review of Native Authenticity: Transnational Perspectives on Native American Literary Studies, ed. Deborah L. Madsen (Albany: State U of New York P, 2010) Fadia Faqir Speaks with Maria Assif: Literature, the Arab Diaspora, Gender and Politics Norman Ravvin Talks to Krzysztof Majer: Absent Fathers, Outsider Perspectives and Yiddish Typewriters